How do you solve the system 5x – 3y = 13 and 4x – 3y = 11?

2 Answers
May 21, 2018

x=2x=2 and y=-1y=1

Explanation:

After subtracting second equation from first one,

(5x-3y)-(4x-3y)=13-11(5x3y)(4x3y)=1311

x=2x=2

Hence,

5*2-3y=13523y=13

10-3y=13103y=13

-3y=33y=3, thus y=3/(-3)=-1y=33=1

May 21, 2018

(2, -1)(2,1)

Explanation:

Solving by Elimination

Multiply the first equation by -11 to temporarily eliminate yy. Then add to the second equation (unmodified).

-(5x - 3y = 13)(5x3y=13)
-5x + 3y = -135x+3y=13
4x - 3y = 114x3y=11

-x = -2x=2
x = 2x=2

Substitute into either equations to solve for yy
5(2) - 3y = 135(2)3y=13
10 - 3y = 13103y=13
- 3y = 3 3y=3
y = -1y=1

Answer: (2, -1)(2,1)